A strategy for entry to the markets of Middle East and North Africa countries (by case of the veterinary market in the Kingdom of Morocco) - Gacim, S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
Markets of Middle East and North Africa (MENA) are very promising ones for Ukrainian exporters. Yet, by now these markets have been closed for most part of the Ukrainian producers because of: misunderstanding of the market specifics in this region and apprehensions of business failures or financial losses, misevaluation of own competitiveness in this region due to great many failed attempts of the market entry. Being attractive for Ukrainian exports, MENA markets need to be approached by prudent strategies. The purpose of the article is to develop and propose a strategy for entry of Ukrainian producers to MENA markets by case of the veterinary market of the Kingdom of Morocco. The proposed strategy, “National Professionals’ Unity Strategy” relies on public professional unions as a guide of exporters to external markets by setting up relations with relevant professional unions abroad. This strategy involves entry to the market of one coun- try (a startup country) with the chain expansions of exports in other MENA countries. The Kingdom of Morocco is proposed as a startup country because of its political and economic stability, good business and investment climate, being an important premise for international cooperation. The strategy covers three consecutive phases: analysis and evaluation; entry to a new market and promotion; chain expansion of exports to other countries of the region. A detailed description of each phase is given. A comprehensive diagnostics of the Moroccan market of disinfectants, fodder additives and veterinary drugs was made. The potential niches for Ukrainian exports to the Kingdom of Morocco were identified. The problems to be faced by potential Ukrainian exporters of veterinary drugs are highlighted. Statistical data on global exports of fodder additives and disinfectants to the Kingdom of Morocco, Tunisia, Egypt and Algeria, with the share of EU (for 2016) are supplied as an evidence to good potentials of MENA markets for Ukrainian exporters. It is concluded that the proposed strategy, as a premise to market entry in the MENA context, can be effectively applied in other regional markets, in African continent in particular.